Preparation method of core-shell high-energy metal fuel under field activation condition

Through the synergistic action of mechanochemical coating and field activation reaction, core-shell high-energy metal fuel is prepared, solving the energy density, stability and safety of existing high-energy fuels, and achieving efficient and controllable fuel production.

CN120236800APending Publication Date: 2025-07-01UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510383045.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

The existing high-energy fuels have challenges in energy density, stability and safety. The traditional improvement methods have problems such as high cost, complex processes, insufficient performance, and unstable combustion of metal fuels such as Mg powder and difficult to store.

Method used

The coordinated action of mechanochemical coating and field activation reaction is adopted to prepare core-shell high-energy metal fuel through high-energy ball milling, solution mixing and spray drying, and the metal-halogen interface reaction is activated by temperature field or plasma field to form a high-crystalline metal halide coating.

Benefits of technology

It simplifies the production process, reduces costs, improves the energy density, thermal reaction activity and combustion stability of the fuel, enhances the antioxidant and environmental adaptability, and meets the high-performance needs of different application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120236800A_ABST
    Figure CN120236800A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a core-shell type high-energy metal fuel under a field activation condition, accurate regulation and control of fuel components and energy release characteristics are realized through a synergistic effect of mechanochemical coating and field activation reaction, firstly, a C / M core-shell structure is constructed through high-energy ball milling, then, halogen-containing compounds (PFPE, PVDF, AP and the like) are dissolved in a specific solvent, and the core-shell type high-energy metal fuel is prepared. Then mixing with C / M powder to form a precursor solution, carrying out ultrasonic-assisted dispersion and spray granulation to obtain halogen-containing compound coated C / M composite powder, finally putting the C / M coated halogen-containing compound in an environment such as a temperature field or a plasma field, and inducing a metal-halogen interface reaction to generate a high-crystallinity metal halide coating layer, so as to obtain the halogen-containing compound coated metal halide coating layer. The high-energy metal halide coated core-shell metal fuel is obtained. According to the method, extra energy is provided through field activation to promote the reaction, the process controllability is high, the product structure can be accurately regulated and controlled, and the method is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energetic materials, and particularly to a preparation method of core-shell high-energy metal fuel under field activation conditions. Background Art

[0002] High-energy fuels are crucial for improving the performance of weapons and equipment. However, current fuels often pose many challenges in terms of energy density, stability, and safety, and it is difficult to meet the requirements of high performance and low risk.

[0003] To obtain new high-energy fuels, researchers have continuously explored and synthesized new materials. For example, tetrahydrotricyclopentadiene (THTCPD) is a new high-energy density hydrocarbon fuel with a density of 1.05 g·cm -3 , and a net combustion heat of 44.7 MJ·L -1 . It has excellent application prospects. Compared with traditional hydrocarbon fuels, JP-10, whose main component is THTCPD, has an energy density of about 47.6 MJ / kg and is commonly used in missiles, engines, and hypersonic aircraft. At the same time, researchers incorporated high-energy solid particles such as B, Be, Al, and Fe into JP-10 for improvement and found that factors such as the type, size, and content of metal particles significantly affect the surface combustion characteristics of JP-10. 16 wt.% of n-Al particles can increase the combustion efficiency of JP-10 by about 4.27%. Superthermites, which combine the advantages of thermites and nanomaterials, exhibit characteristics such as high energy density, high reaction heat, and fast heat release efficiency. Commonly used ones include Al / CuO, Al / PbO, and Al / Bi2O3, etc. In recent years, a large number of studies on superthermites have been carried out at home and abroad, including aspects such as preparation processes, microstructure regulation, performance characterization, and formulation design. It has been found that applying them to solid propellants can effectively improve the specific impulse and energy release efficiency and improve the ballistic performance. In addition, biomass green high-energy fuels have become a hot research topic in recent years. The main raw material sources include terpene compounds, lignocellulose, and their derivatives. By means of cyclopropanation, polymerization reactions, etc., bridged-ring and spiro-ring are constructed to meet the requirements of high energy density of the fuel. For example, by polymerizing α-pinene, β-pinene, etc. and then hydrogenating, a high-energy fuel with a density of 0.94 g·mL -1 can be obtained; using cyclopentanone as a substrate, a fuel with a density of 0.943 g·mL -1 can be synthesized through a one-pot three-step method. However, the synthesis of these new fuels usually faces problems such as high costs, complex processes, and long cycles, which are not conducive to large-scale production and application.

[0004] Among existing high-energy fuels, Mg powder has been widely studied and applied. However, it has problems such as unstable combustion, high sensitivity, and difficulties in storage and handling, which limit its wider use. To improve its performance, measures such as surface coating, compounding with other materials, and adding stabilizers have been taken. But these methods often have deficiencies such as reducing combustion efficiency, increasing combustion non-uniformity, and poor environmental adaptability.

[0005] Coating a layer of metal powder, such as nanoscale Cu powder, Fe powder, Ag powder, and Ni powder, on the surface of Al powder can improve the antioxidant performance, corrosion resistance, and electrical conductivity of Al powder, and thus improve the combustion performance of the propellant. Some researchers have successfully prepared core-shell structured Ni-Fe / Al composite powder and applied it to HTPE propellant. Measured by a nitrogen target line method burning rate meter, compared with pure Al powder, the burning rates of HTPE propellant containing Ni-Fe / Al composite powder at 3 MPa and 5 MPa increased by 11.8% and 2.07% respectively; under 3 MPa - 9 MPa, the pressure exponent decreased by 31.4%. However, a single metal coating layer may have problems such as oxidation, peeling, or interfacial diffusion reaction with the aluminum core during long-term storage or extreme working conditions (such as high temperature and high humidity). There is also a method of coating Al powder with an organic polymer and then using one or several of light, heat, and plasma conditions to excite a fluorinating agent to cause the polymer to undergo a fluorination reaction, and then obtaining a reaction product. This method has low toxicity, high safety, and strong operability, but at the same time has problems such as insufficient fluorination or overreaction, and the coating layer is prone to degradation and failure under high temperature and other working conditions. Summary of the Invention

[0006] To solve the above problems, the present invention proposes a method for preparing a core-shell type high-energy metal fuel under field activation conditions. This method first uses spray granulation technology to uniformly coat a salt / polymer of a halide on the surface of C / M powder, and then places it in a specific field. Under the action of this specific field, the energy distribution in the system changes, and the activity of molecules or atoms is excited, thus greatly promoting the progress of chemical reactions. This field activation method has high efficiency and pertinence, can accelerate the reaction process under relatively mild conditions, and avoids problems such as overreaction or incomplete reaction that may occur in traditional methods.

[0007] A method for preparing a core-shell type high-energy metal fuel under field activation conditions, the method comprising:

[0008] Step S1, weighing metal C powder and metal M powder according to a set atomic ratio, and mechanically ball-milling to coat spherical M powder on the surface of spherical C powder to form C / M powder with a core of C and a shell of M structure;

[0009] Step S2: Dissolve the halogen-containing compound in a solvent, and magnetically stir it at a temperature of 20°C - 80°C for 0.5 h - 2.5 h until it is completely dissolved to form a homogeneous solution;

[0010] Step S3: Then add the C / M powder from Step S1 to the homogeneous solution in Step S2, and stir it at a temperature of 20°C - 80°C for 0.5 h - 2.5 h until the C / M powder is completely dispersed in the solution to obtain a precursor solution;

[0011] Step S4: Spray-dry the precursor solution obtained in Step S3 to obtain spherical core-shell powder of C / M coated with a halogen-containing compound with a particle size distribution of 1 μm - 50 μm, namely C / M@halogen-containing compound;

[0012] Step S5: Place the C / M@halogen-containing compound obtained in Step S4 in a temperature field or a plasma field to induce a metal-halogen interfacial reaction to generate a metal fuel coated with a metal halide.

[0013] Furthermore, the metal C powder is one or more of low and medium melting point metals, with its melting point ≤ 800°C, including Al, Mg, and Li; the metal M powder is a highly catalytically active transition metal or its alloy, including Cu, Fe, Ni, Ag, Fe3Ni, and Ag7Cu3.

[0014] Furthermore, in Step S1, the molar ratio of the metal C powder to the metal M powder is 1:1 to 1:7, and this ratio affects the thermal reaction activity of metal combustion.

[0015] Furthermore, the ball milling device in Step S1 includes a grinding tank, grinding balls, and a mechanical drive system. The grinding parameters are set as follows: the ball-to-powder weight ratio is 5:1 to 20:1, the grinding time is 1 h - 6 h, the rotation speed is 150 rpm - 400 rpm, and the grinding process is carried out in an inert argon atmosphere.

[0016] Furthermore, in Step S2, the mass fraction of the halogen-containing compound is 2% to 50%, the halogen-containing compound includes PFPE, PVDF, AP, and the solvent includes deionized water.

[0017] Furthermore, in Step S3, the inlet and outlet temperatures of the spray drying equipment are respectively controlled and maintained at 100°C - 130°C and 130°C - 170°C.

[0018] Furthermore, the conditions for heat treatment in the temperature field in Step S4 are as follows: in an argon atmosphere, slowly heat it to 380°C - 420°C, and the heating rate is 3°C·min -1 -15°C·min -1 , and the holding time is 0.5 h - 4 h.

[0019] In step S3, the stirring temperature range is wide, which can adapt to different reaction conditions, and the stirring time is appropriate, effectively ensuring the sufficient dispersion of C / M in the solution and laying a foundation for the subsequent formation of a stable precursor solution.

[0020] In step S4, the drying treatment method of the precursor solution is simple and efficient, which is conducive to the large-scale production of salt or polymer-coated C / M spherical powder.

[0021] In step S5, the treatment by temperature field or plasma field is advanced and unique, and can accurately realize the transformation from salt or polymer-coated C / M spherical powder to core-shell type high-energy metal halide-coated metal fuel.

[0022] Compared with the prior art, the beneficial technical effects of the present invention are as follows:

[0023] First of all, in terms of process design, through the synergistic effect of mechanochemical coating and field-activated reaction, the traditional multi-step and high-cost preparation process is simplified into efficient steps such as high-energy ball milling, solution mixing, spray drying and field activation treatment, greatly reducing the production cost and improving the process controllability; secondly, by accurately regulating the molar ratio of the core metal to the shell metal and combining the uniform coating of halogen-containing compounds (halide salts or polymers), the optimized design of the core-shell structure is realized, significantly improving the energy density, thermal reaction activity and combustion stability of the fuel; in addition, the field activation technology (such as temperature field or plasma field) stimulates the interfacial reaction under mild conditions, avoiding the overreaction or structural damage caused by traditional high-temperature treatment, and at the same time enhancing the antioxidant property and environmental adaptability through the halide coating layer, solving the problems of unstable combustion and difficult storage of metal fuels (such as Mg powder); furthermore, the raw material selection and process route of the present invention pay attention to environmental protection, using non-toxic or low-toxic halides and adjustable solvents, reducing the generation of harmful waste, and meeting the requirements of green and sustainable development; finally, the solution of the present invention has high flexibility and scalability. By adjusting the combination of the core metal and the shell metal, the type of halide and the field activation parameters, the energy release characteristics of the fuel can be regulated to meet the requirements of different scenarios such as missile propellants and hypersonic aircraft for high-performance fuels. In summary, the present invention has achieved technological breakthroughs in aspects such as process simplification, performance improvement, stability enhancement and environmental protection, providing an efficient, controllable and highly adaptable innovative solution for the field of high-energy fuels. Description of the Drawings

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0025] Figure 1 is a schematic process flow diagram for preparing Al / Ni provided in Embodiment 1 of the present invention;

[0026] Figure 2 is a schematic process flow diagram for preparing Al / Ni@NiCl2 composite material provided in Embodiment 1 of the present invention;

[0027] Figure 3 are SEM images and EDS spectra of the Al / Ni and Al / Ni@NiCl2 composite materials prepared in Example 1 of the present invention. Among them, Figure 3 in (a) is the SEM image of the Al / Ni mixture after high-energy ball milling, Figure 3 in (b) is the SEM image of the Al / Ni@AP composite after heat treatment at 400 °C, Figure 3 in (b1)-(b7) are the distribution maps of Al / Ni@NiCl2, Al, Ni, Cl, O, C, and N elements on the sample surface respectively, Figure 3 in (b8) is the EDS energy spectrum analysis chart of Al / Ni@NiCl2. Detailed implementation manners

[0028] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0029] The present invention proposes a method for preparing a core-shell type high-energy metal fuel under field activation conditions. First, C powder and M powder are fully mixed according to a specific ratio and process to prepare a uniform C / M powder. Subsequently, the halogen-containing compound is dissolved in a specific solution to make the halogen-containing components fully and evenly dispersed. Then, the prepared C / M powder is added thereto, and through sufficient stirring, the C / M powder is brought into full contact and interaction with the halogen-containing compound solution, thereby obtaining a precursor solution with uniform composition. After that, the precursor solution is dried to remove the solvent therein, so that the halogen-containing compound adheres tightly to the surface of the C / M powder, forming a preliminary coating structure.

[0030] Finally, the dried product is placed in a selected specific field. Under the action of the specific field, the activity of the substances in the system is excited, and the intermolecular interaction is enhanced, thereby promoting the efficient progress of the chemical reaction, enabling the halogen-containing compound to further react and firmly combine with the C / M powder, and finally forming a metal fuel coated with a core-shell type high-energy metal halide.

[0031] The technical solution for preparing core-shell high-energy metal fuel under in-situ activation conditions will be described in detail below through specific examples.

[0032] Example 1

[0033] A preparation method of core-shell high-energy metal fuel Al / Ni@NiCl2 under in-situ activation conditions includes the following steps:

[0034] Preparation of Al / Ni, as Figure 1 shown: The atomic ratio of Al to Ni is 1:1. The Al / Ni nanocomposite is prepared by mechanical ball milling using a planetary high-energy ball milling facility. The ball milling device includes a grinding jar, grinding balls, and a mechanical drive system. The key grinding process parameters are set as follows: the ball-to-powder weight ratio is 10:1, the grinding time is 2 h, and the rotation speed is 250 rpm. To prevent powder oxidation, the grinding process is carried out in an inert argon atmosphere.

[0035] Preparation of Al / Ni@NiCl2, as Figure 2 shown: First, a core-shell structured Al / Ni@AP composite is prepared by spray drying technology. Ammonium perchlorate (AP) is first dissolved in deionized water and magnetically stirred for 0.5 h until AP is completely dissolved. Subsequently, the Al / Ni composite powder previously prepared by high-energy ball milling is added to the solution. Then the resulting mixture is magnetically stirred for another 2 h to ensure uniform dispersion of the powder. Finally, the Al / Ni@AP composite is obtained by spray drying technology. The specific parameters of the spray drying technology are as follows: The precursor solution is fed into the atomizer at a flow rate of 8 mL·min -1 . Meanwhile, the inlet and outlet temperatures of the spray drying equipment are controlled and maintained at 110 °C and 150 °C, respectively.

[0036] Subsequently, the obtained Al / Ni@AP composite is transferred to a tube furnace for heat treatment. Under an argon atmosphere, it is slowly heated to 400 °C at a heating rate of 10 °C·min -1 , and the holding time is 1 h. During the heat treatment process, an interaction occurs between Al / Ni and the pyrolysis gas-phase products of AP, thereby forming Al / Ni@NiCl2.

[0037] The core-shell high-energy metal fuel Al / Ni@NiCl2 prepared in Example 1 is analyzed by scanning electron microscopy (SEM). Its crystal morphology is as Figure 3 shown in (a)-(b). As can be seen from Figure 3 (a) therein, smaller Ni particles are evenly adhered to larger Al particles, and the original morphologies of Al and Ni are retained. After heat treatment of the Al / Ni@AP composite at 400 °C, AP decomposes, thereby releasing a large amount of gaseous products. As can be seen from Figure 3As can be seen from (b) in [reference], these gases interact with the Al / Ni composite material to form a unique honeycomb-like porous microsphere structure.

[0038] Perform energy spectrum analysis (EDS) on a core-shell high-energy metal fuel Al / Ni@NiCl2 prepared in Example 1 under field activation conditions. The results are as Figure 3 shown in (b1)-(b8) of [figure], and it is found that the surface of these honeycomb-like porous microsphere structures is mainly composed of elements such as Cl, Al, and Ni. The results of the energy spectrum map provide strong evidence for the reaction between the AP pyrolysis products and Al / Ni. This unique structure significantly increases the specific surface area of the composite material and improves its thermal reactivity.

[0039] Example 2

[0040] A preparation method of a core-shell high-energy metal fuel Al / Ni@NiCl2 under field activation conditions includes the following steps:

[0041] Preparation of Al / Ni: The atomic ratio of Al to Ni is 1:1. Use a planetary high-energy ball milling facility to prepare the Al / Ni nanocomposite material by mechanical ball milling. The ball milling device includes a grinding jar, grinding balls, and a mechanical drive system. The key grinding process parameters are set as follows: the ball-to-powder weight ratio is 20:1, the grinding time is 1 h, the rotation speed is 400 rpm. To prevent powder oxidation, the grinding process is carried out in an inert argon atmosphere.

[0042] Preparation of Al / Ni@NiCl2: First, prepare a core-shell structured Al / Ni@AP composite material by spray drying technology. First, dissolve AP in deionized water and stir magnetically for 0.5 h until AP is completely dissolved. Subsequently, add the Al / Ni composite powder previously prepared by high-energy ball milling into the solution. Then stir the obtained mixture magnetically for another 2 h to ensure uniform dispersion of the powder. Finally, obtain the Al / Ni@AP composite material through spray drying technology. The specific parameters of the spray drying technology are as follows: Use a peristaltic pump to feed the precursor solution into the atomizer at a flow rate of 12 mL·min -1 . At the same time, the inlet and outlet temperatures of the spray drying equipment are controlled and maintained at 100 °C and 130 °C respectively.

[0043] Subsequently, transfer the obtained Al / Ni@AP composite material to a tubular furnace for heat treatment. Under an argon atmosphere, slowly heat it to 380 °C at a heating rate of 15 °C·min -1 , and the holding time is 0.5 h. During the heat treatment process, an interaction occurs between Al / Ni and the AP pyrolysis gas-phase products, thus forming Al / Ni@NiCl2.

[0044] Example 3

[0045] A preparation method of core-shell high-energy metal fuel Al / Ni@NiCl2 under field activation conditions, comprising the following steps:

[0046] Preparation of Al / Ni: The atomic ratio of Al to Ni is 1:1. Al / Ni nanocomposites are prepared by mechanical ball milling using a planetary high-energy ball milling facility. The ball milling device includes a grinding tank, grinding balls, and a mechanical drive system. The key grinding process parameters are set as follows: the ball-to-powder weight ratio is 5:1, the grinding time is 6 h, and the rotation speed is 150 rpm. To prevent powder oxidation, the grinding process is carried out in an inert argon atmosphere.

[0047] Preparation of Al / Ni@NiCl2: First, core-shell structured Al / Ni@AP composites are prepared by spray drying technology. First, AP is dissolved in deionized water and magnetically stirred for 0.5 h until AP is completely dissolved. Subsequently, the Al / Ni composite powder previously prepared by high-energy ball milling is added to the solution. Then the resulting mixture is magnetically stirred for another 2 h to ensure uniform dispersion of the powder. Finally, Al / Ni@AP composites are obtained by spray drying technology. The specific parameters of the spray drying technology are as follows: The precursor solution is fed into the atomizer at a flow rate of 3 mL·min -1 and at the same time, the inlet and outlet temperatures of the spray drying equipment are controlled and maintained at 130 °C and 170 °C respectively.

[0048] Subsequently, the obtained Al / Ni@AP composites are transferred to a tubular furnace for heat treatment. Under an argon atmosphere, it is slowly heated to 420 °C at a heating rate of 3 °C·min -1 and the holding time is 4 h. During the heat treatment process, an interaction occurs between Al / Ni and the pyrolysis gas-phase products of AP, thus forming Al / Ni@NiCl2.

[0049] Example 4

[0050] A preparation method of core-shell high-energy metal fuel Al / Ni@NiCl2 under field activation conditions, comprising the following process steps:

[0051] Preparation of Al / Ni: The atomic ratio of Al to Ni is 1:1. Al / Ni nanocomposites are prepared by mechanical ball milling using a planetary high-energy ball milling facility. The ball milling device includes a grinding tank, grinding balls, and a mechanical drive system. The key grinding process parameters are set as follows: the ball-to-powder weight ratio is 10:1, the grinding time is 3 h, and the rotation speed is 200 rpm. To prevent powder oxidation, the grinding process is carried out in an inert argon atmosphere.

[0052] Preparation of Al / Ni@NiCl2: First, a core-shell structured Al / Ni@AP composite material was prepared by spray drying technology. First, AP was dissolved in deionized water and magnetically stirred for 0.5 h until AP was completely dissolved. Subsequently, the Al / Ni composite powder previously prepared by high-energy ball milling was added to the solution. Then the resulting mixture was magnetically stirred for another 2 h to ensure uniform dispersion of the powder. Finally, the Al / Ni@AP composite material was obtained by spray drying technology. The specific parameters of the spray drying technology are as follows: The precursor solution was fed into the atomizer at a flow rate of 6 mL·min -1 and the inlet and outlet temperatures of the spray drying equipment were controlled and maintained at 115 °C and 145 °C, respectively.

[0053] Subsequently, the obtained Al / Ni@AP composite material was transferred to a tubular furnace for heat treatment. Under an argon atmosphere, it was slowly heated to 400 °C at a heating rate of 8 °C·min -1 and the holding time was 2 h. During the heat treatment process, an interaction occurred between Al / Ni and the pyrolysis gas-phase products of AP, thus forming Al / Ni@NiCl2.

[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements for some or all of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a core-shell high-energy metal fuel under field activation conditions, characterized in that: The method comprises: Step S1, weighing metal C powder and metal M powder according to a set atomic ratio, and coating the spherical M powder on the surface of the spherical C powder by mechanical ball milling to form a C / M powder with C as the core and M as the shell structure; Step S2, dissolving the halogen-containing compound in a solvent, and magnetically stirring at a temperature of 20° C. to 80° C. for 0.5 h to 2.5 h until the compound is completely dissolved to form a homogeneous solution; Step S3, adding the C / M powder of step S1 to the homogeneous solution of step S2, stirring at a temperature of 20° C. to 80° C. for 0.5 h to 2.5 h until the C / M powder is completely dispersed in the solution, to obtain a precursor solution; Step S4, spray drying the precursor solution obtained in step S3 to obtain C / M spherical core-shell powder coated with a halogen-containing compound with a particle size distribution of 1 μm-50 μm, namely, C / M@halogen-containing compound; Step S5, placing the C / M@ halogen-containing compound obtained in step S4 in a temperature field or a plasma field to induce a metal-halogen interface reaction to generate a metal fuel coated with a metal halide.

2. The method according to claim 1, characterized in that: The metal C powder is one or more low- and medium-melting-point metals, and its melting point is required to be ≤800°C, including Al, Mg and Li; the metal M powder is a high-catalytically active transition metal or its alloy, including Cu, Fe, Ni, Ag, Fe3Ni and Ag7Cu3.

3. The method according to claim 1, characterized in that In step S1 , the molar ratio of the metal C powder to the metal M powder is 1:1 to 1:7, and the ratio affects the thermal reaction activity of the metal combustion.

4. The method according to claim 1, characterized in that In step S1, the ball milling device includes a grinding jar, grinding balls and a mechanical drive system. The grinding parameters are set as follows: the ball-to-powder weight ratio is 5:1 to 20:1, the grinding time is 1h-6h, the rotation speed is 150rpm-400rpm, and the grinding process is carried out in an inert argon atmosphere.

5. The method according to claim 1, characterized in that In step S2, the mass fraction of the halogen-containing compound is 2% to 50%, the halogen-containing compound includes PFPE, PVDF, and AP, and the solvent includes deionized water.

6. The method according to claim 1, characterized in that In step S3, the inlet and outlet temperatures of the spray drying equipment are controlled and maintained at 100°C-130°C and 130°C-170°C respectively.

7. The method according to claim 1, characterized in that The temperature field heat treatment conditions in step S4 are: slowly heating it to 380℃-420℃ in an argon atmosphere at a heating rate of 3℃·min -1 -15℃·min -1 , the insulation time is 0.5h-4h.